2021
DOI: 10.1111/ajsp.12506
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and indebtedness: Associations with personality traits and life satisfaction in South Korea

Abstract: Gratitude and indebtedness are predominant emotional and cognitive responses that occur after receiving benefits from others. There is ambiguity as to whether these two emotions are distinct in interdependence‐oriented cultures. To investigate whether gratitude and indebtedness are distinct emotions in South Korea, we examined the relationship between gratitude and indebtedness and the associations between these emotions and personality traits. Further, we examined the relationships of gratitude and indebtedne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A sense of indebtedness is the obligation to repay another, which is often a relatively stable and lasting emotional state after receiving support from others and society [ 42 , 43 ]. Different individuals differ significantly in their sense of indebtedness after receiving [ 44 , 45 ]. The greater the state of indebtedness, the greater the pressure to compel individuals to provide feedback to others [ 46 ] to seek a balance in social interaction and achieve the goal of mutual benefit, equality, and fairness [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…A sense of indebtedness is the obligation to repay another, which is often a relatively stable and lasting emotional state after receiving support from others and society [ 42 , 43 ]. Different individuals differ significantly in their sense of indebtedness after receiving [ 44 , 45 ]. The greater the state of indebtedness, the greater the pressure to compel individuals to provide feedback to others [ 46 ] to seek a balance in social interaction and achieve the goal of mutual benefit, equality, and fairness [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that a higher inclination towards feeling indebted is associated with lower levels of life satisfaction [19,20]. However, further research has demonstrated that after accounting for the Big Five personality traits, the negative correlation between indebtedness and life satisfaction becomes statistically insigni cant [21]. These ndings suggest that while indebtedness may have certain negative psychological consequences, its impact is not universally absolute.…”
Section: Introductionmentioning
confidence: 99%